2018
DOI: 10.1016/j.celrep.2017.12.078
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 Promotes DNA Repair and Mediates the Formation of TMPRSS2-ERG Gene Rearrangements in Prostate Cancer

Abstract: SummaryBRD4 belongs to the bromodomain and extraterminal (BET) family of chromatin reader proteins that bind acetylated histones and regulate gene expression. Pharmacological inhibition of BRD4 by BET inhibitors (BETi) has indicated antitumor activity against multiple cancer types. We show that BRD4 is essential for the repair of DNA double-strand breaks (DSBs) and mediates the formation of oncogenic gene rearrangements by engaging the non-homologous end joining (NHEJ) pathway. Mechanistically, genome-wide DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 49 publications
6
102
0
Order By: Relevance
“…Recently, BET inhibitors have been reported to hamper DNA damage repair through several distinct mechanisms. Li et al . reported that BRD4 participated in NHEJ DNA repair by regulating NHEJ DNA repair genes and interacting with NHEJ DNA repair proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, BET inhibitors have been reported to hamper DNA damage repair through several distinct mechanisms. Li et al . reported that BRD4 participated in NHEJ DNA repair by regulating NHEJ DNA repair genes and interacting with NHEJ DNA repair proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, BET inhibitors have been reported to hamper DNA damage repair through several distinct mechanisms. Li et al 17 reported that BRD4 participated in NHEJ DNA repair by regulating NHEJ DNA repair genes and interacting with NHEJ DNA repair proteins. Wang et al 33 discovered a BRD-like module in the catalytic subunit of DNA-dependent protein kinase (DNA-PKcs-BRD) to which JQ1 could bind and further showed that JQ1 hampered NHEJ DNA repair by impairing DNA-PKcs activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemistry (IHC) for BRD4, AR-V7 and full length androgen receptor (AR-FL) was performed on patient samples and CP50 PDX as previously described (Supplementary Methods) (25,26,43).…”
Section: Tissue Analysismentioning
confidence: 99%